Should we abandon the APTT for monitoring unfractionated heparin?. Issue 157 (September 2017) - Arachchillage, D.R.J.; Kamani, F.; Deplano, S.; Banya, W.; Laffan, M.
Abstract: Introduction: The activated partial thromboplastin time (APTT) is commonly used to monitor unfractionated heparin (UFH) but may not accurately measure the amount of heparin present. The anti-Xa assay is less susceptible to confounding factors and may be a better assay for this purpose. Materials and methods: The validity of the APTT for monitoring UFH was assessed by comparing with an anti-Xa assay on 3543 samples from 475 patients (infants [n = 165], children 1–15 years [n = 60] and adults [n = 250]) receiving treatment dose UFH. Results: Overall concordance was poor. The highest concordance (66%; 168/254) was seen in children. Concordance (51.8%) or discordance (48.4%) was almost equal in adult patients. Among adult patients whose anti-Xa level was within 0.3–0.7 IU/mL, only 38% had an APTT in the therapeutic range whilst 56% were below and 6% were above therapeutic range. Children and adult patients with anti-Xa of 0.3–0.7 IU/mL but sub- therapeutic APTT had significantly higher fibrinogen levels compared to those with therapeutic or supra-therapeutic APTT. Conclusions: When the anti-Xa level was 0.3–0.7 IU/mL, the majority of samples from infants demonstrated a supra-therapeutic APTT, whilst adults tended to have a sub-therapeutic APTT. This may lead to under anticoagulation in infants or over anticoagulation in adults with risk of bleeding if APTT is used to monitor UFH. These results further strengthen existing evidence of the limitation of APTT in monitoring UFH. Discordance of APTT and anti-Xa level in adults and children may be due to elevation of fibrinogen level. Highlights: Use of APTT in monitoring unfractionated heparin was compared with anti-Xa assay. Concordance was poor between APTT and heparin anti-Xa levels in all age groups. The majority of infants had supra-therapeutic APTT with anti-Xa level 0.3–0.7 IU/mL. Adults tended to have a sub-therapeutic APTT when anti-Xa level of 0.3–0.7 IU/mL. Under-responsiveness APTT in adults & children may be partly due to raised fibrinogen.